Rancang Bangun Mesin Penetas Telur Otomatis Dengan Perata Suhu Kipas Casing CPU (UNHASY, 2022)
Egg Incubator is a tool that helps the process of hatching eggs. With the egg incubator then the eggs can be hatched without going through the incubation process by the help of the parent. Hatching eggs in principle is to provide a suitable environment so that poultry eggs can hatch. This Egg Incubator aims to increase hatching power with an automatic egg screening system and digital temperature control. With the incubator is able to increase the percentage of success ranges from 80-85% in the process of hatching eggs. In the research of automatic Egg Incubator design with temperature grader CPU casing fan with a capacity of 25 this method used is the method of R&D(research and development). This study authors use a type of digital thermostat that aims to set the temperature stability in accordance with the provisions. Testing tools using descriptive method by asking some questions or questionnaires to the validator. The results of this study obtained the test results of several components and the time required to hatch eggs. The average required component testing shows good performance. While the average testing percentage of hatching eggs showed 82.5%. In the feasibility test and functional tools will be validated by Mr / Ms lecturer (validator). The average amount of percentage tested by validator 1 and validator 2 is 93.5% for feasibility testing. While functional testing the average amount of presntase tested by validator 1 and validator 2 is 93%. So the results of the feasibility and functional testing of the tool validated by 2 validators on the tool are categorized as very good.